PENGARUH PENGEMBANGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA DENGAN VARIBEL MODERASI BEBAN KERJA PADA DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN LABUHAN BATU - Tarigan, Armansyah; Nasution, Zulkarnain; Hutagaol, Anita Sri Rejeki (Jurnal Investasi, 2025)
This study aims to explore the influence of work development and work motivation on employee performance by considering workload as a moderating variable. In an ever-evolving work environment, employee skill development and increased work motivation are important elements in supporting performance. However, workload is often a challenge that can affect the effectiveness of both factors. This study uses a quantitative approach with a survey method involving 50 respondents. Data were analyzed using moderated regression techniques to illuminate direct relationships and interactions between variables with smartpls.